2013
DOI: 10.1248/bpb.b13-00046
|View full text |Cite
|
Sign up to set email alerts
|

Glycolaldehyde Induces Cytotoxicity and Increases Glutathione and Multidrug-Resistance-Associated Protein Levels in Schwann Cells

Abstract: Schwann cell injury is observed in diabetic neuropathy. It is speculated that glycolaldehyde (GA), a precursor of advanced glycation end products (AGEs), contributes to the pathogenesis and development of diabetic neuropathy. Here, we demonstrated for the first time that GA at near-physiological concentration decreased the viability of rat Schwann cells. In contrast, methylglyoxal, glyoxal, and 3-deoxyglucosone, all of which are AGE precursors, had no effects on cell viability. It is well known that methylglyo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
22
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(25 citation statements)
references
References 28 publications
0
22
0
Order By: Relevance
“…The formation of AGEs by reactive dicarbonyls has been recognized to play an important role in the pathogenesis of sensory neuron damage [148]. It has shown that glycolaldehyde (a precursor of AGEs) at physiological concentration decreases the viability of rat Schwann cells, thus contributes to the pathogenesis and development of diabetic neuropathy [149]. Increased tissue and cellular glucose levels also stimulate glycolytic and polyol pathways in the peripheral nerve [150].…”
Section: Ages and Diabetic Complicationsmentioning
confidence: 99%
“…The formation of AGEs by reactive dicarbonyls has been recognized to play an important role in the pathogenesis of sensory neuron damage [148]. It has shown that glycolaldehyde (a precursor of AGEs) at physiological concentration decreases the viability of rat Schwann cells, thus contributes to the pathogenesis and development of diabetic neuropathy [149]. Increased tissue and cellular glucose levels also stimulate glycolytic and polyol pathways in the peripheral nerve [150].…”
Section: Ages and Diabetic Complicationsmentioning
confidence: 99%
“…There is only one report showing that GA induces apoptosis via oxidative stress in breast cancer cells [16] . On the other hand, we have reported that oxidative stress is not a major contributor to the GA-induced cytotoxicity in Schwann cells [12] . Endoplasmic reticulum (ER) stress was found to be involved in the induction of apoptosis that occurs in a wide range of metabolic diseases, including diabetes mellitus [17] .…”
Section: Introductionmentioning
confidence: 76%
“…It is reported that AGEs and MG induce apoptosis in Schwann cells [7] , [8] , [11] . In our previous report, we demonstrated that GA decreased the viability of rat Schwann cells [12] . Moreover, GA had a greater effect on Schwann cells than dicarbonyl compounds, such as MG.…”
Section: Introductionmentioning
confidence: 79%
See 1 more Smart Citation
“…AGEs were found in the peripheral nerves of diabetic rats, and the expression of RAGE was found in endothelial and Schwann cells, which may be responsible for impaired nerve function and pathological nerve alterations [26]. Glycolaldehyde (a precursor of AGEs) at physiological concentrations can decrease the viability of rat Schwann cells and thereby contribute to the pathogenesis and development of diabetic neuropathy [27].…”
Section: Introductionmentioning
confidence: 99%